2008
DOI: 10.1182/blood-2006-11-060632
|View full text |Cite
|
Sign up to set email alerts
|

Reduced activation of protein kinase B, Rac, and F-actin polymerization contributes to an impairment of stromal cell–derived factor-1–induced migration of CD34+ cells from patients with myelodysplasia

Abstract: Patients with myelodysplasia (MDS) show a differentiation defect in the multipotent stem-cell compartment. An important factor in stem-cell differentiation is their proper localization within the bone marrow microenvironment, which is regulated by stromal cell-derived factor (SDF-1). We now show that SDF-1-induced migration of CD34 ؉ progenitor cells from MDS patients is severely impaired. In addition, these cells show a reduced capacity to polymerize F-actin in response to SDF-1. We demonstrate a major role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 53 publications
1
48
1
1
Order By: Relevance
“…7 Strong CXCL12 expression by CD271 þ ALP þ MSCs could be a source of abnormal survival/proliferation signaling for adjacent neoplastic CD34 þ HSPCs. CXCL12 is also involved in hematopoietic stem cell homing, 27 and isolated CD34 þ HSPCs from MDS patients are impaired in their ability to migrate toward CXCL12, 51 a finding that is associated with increased susceptibility to apoptosis in vitro. 28 Increased CXCL12 expression by MSCs could be part of a defective feedback loop between neoplastic CD34 þ HSPCs and altered MSCs in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…7 Strong CXCL12 expression by CD271 þ ALP þ MSCs could be a source of abnormal survival/proliferation signaling for adjacent neoplastic CD34 þ HSPCs. CXCL12 is also involved in hematopoietic stem cell homing, 27 and isolated CD34 þ HSPCs from MDS patients are impaired in their ability to migrate toward CXCL12, 51 a finding that is associated with increased susceptibility to apoptosis in vitro. 28 Increased CXCL12 expression by MSCs could be part of a defective feedback loop between neoplastic CD34 þ HSPCs and altered MSCs in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…In inhibition experiments, we could identify PI3K as one player in this process. PI3K was reported to be involved in the signaling cascade downstream of integrins (Giancotti and Ruoslahti, 1999;Melikova et al, 2004), the inside-out activation of integrins (Chrétien et al, 2010), the regulation of growth factor-dependent migration of cells (Fuhler et al, 2008;Zhang et al, 2001) and the mechanosensitive pathways induced by strain in endothelial, epithelial and muscle cells (Chrétien et al, 2010;Gayer et al, 2009;Pardo et al, 2008). All these processes might play a role in the transduction of a mechanical into a biochemical signal and the cell response with altered migration and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…4D). In order to delineate the signaling cues for this mechanosensing process, we targeted phosphatidylinositol-3-kinase (PI3K), which is involved in the regulation of cell adhesion, migration and mechanotransduction processes (Chrétien et al, 2010;Fuhler et al, 2008;Gayer et al, 2009;Giancotti and Ruoslahti, 1999;Melikova et al, 2004;Pardo et al, 2008;Zhang et al, 2001). Inhibition of PI3K with LY294002 impaired cell adhesion on both soft and hard gels.…”
Section: Adrenergic Stimulation Of Osteoblasts Induces Cell Stiffeningmentioning
confidence: 99%
“…Many studies have reported a cross-talk between Rho-GTPases and PI3K (Fuhler et al, 2008;Li et al, 2005;Servant et al, 2000). Rac is a member of the Rho family small GTP-binding proteins, which regulate the assembly of actin cytoskeletal structures associated with cell migration (Small et al, 1999), and is known to be a downstream signal of PI3K (Hall, 1998;Li et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%